Genetic outcomes from the translocations of the critically endangered woylie - Pacioni, Carlo; Wayne, A.; Spencer, P. (2013)
Translocations are an important conservation strategy for many species. However simply observing demographic growth of a translocated population is not sufficient to infer species recovery. Adequate genetic representation of the source population(s) and their long-term viability should also be considered. The woylie Bettongia penicillata ogilbyi has been subject to more formal translocations for conservation than any other marsupial that, up until recently, has resulted in one of the most successful species recoveries in Australia. We used mitochondrial and nuclear DNA markers to assess the genetic outcomes of translocated woylie populations. These populations have lost genetic variability, differentiated from their source population and the supplementation program on two island populations appears to have failed. We discuss the conservation implications that our results have for managing threatened species, outline some general recommendations for the management of present and future translocations and discuss the appropriate sampling design for the establishment of new populations or captive breeding programs that may mitigate the genetic 'erosion' seen in our study species. This research provides some practical outcomes and a pragmatic understanding of translocation biology. The findings are directly applicable to other translocation programs. © 2013 Current Zoology.